أثر ممارسات إدارة الموارد البشرية في تحقيق جودة الخدمة البنكية- دراسة حالة عينة من البنوك النشطة على مستوى ولاية سكيكدة- - لعمامرة, صارة; محبوب, فاطمة (جامعة الوادي - University of Eloued, 2022)
The goal of the study was to determine the impact of human resource management practices on Achieving banking service quality in some active banks in the state of Skikda. To achieve the study's objectives, a three-axis questionnaire was created to collect data and information from a sample of approximately 70 people, which was then, processed using the Statistical Package for Social Sciences programme to extract results and verify hypotheses. The study found that human resource management practices in the four dimensions of employment, training, performance evaluation, and compensation and rewards have a significant and statistically significant impact on Achieving the quality of banking service in the banks studied to varying degrees
Human Resource Management Practices’ Impact on Achieving Banking Service Quality -A Case Study of Several Banks at Skikda State
مقال
Keywords: إدارة الموارد البشرية ; ممارسات إدارة الموارد البشرية ; جودة الخدمة البنكية ; البنوك